2020
DOI: 10.1016/j.tranpol.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of introducing low-cost high-speed rail on air-rail competition: Modelling and numerical analysis for Paris-Marseille

Abstract: Given the trend of railway liberalization in Europe and Asia, we explore the effects of introducing low-cost highspeed rail as an answer to the railway reform on air-rail competition. In particular, by proposing a vertically differentiated model, we first derive the optimal pricing policies as well as the corresponding profits and market shares for low-cost high-speed rail (LCR), full-service high-speed rail (FSR) and air transport (Air). We do so for two types of LCR entrants, namely the incumbent owned entra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Recall that we consider two situations where the entrant is either independently-owned or incumbent-owned. If the entrant belongs to the incumbent, following Wang et al (2020), the new entrant aims to maximize the combined rail profits. The maximization problem for the incumbent-owned entrant can be expressed as:…”
Section: ∂( ∂Qmentioning
confidence: 99%
“…Recall that we consider two situations where the entrant is either independently-owned or incumbent-owned. If the entrant belongs to the incumbent, following Wang et al (2020), the new entrant aims to maximize the combined rail profits. The maximization problem for the incumbent-owned entrant can be expressed as:…”
Section: ∂( ∂Qmentioning
confidence: 99%
“…The effect of HSR development is evident in several sectors, such as economic development [24] and the air transportation industry [1,2,17,18,[25][26][27][28][29][30][31][32][33], as well as the existing conventional railway industry [27]. A study on the competition between transport modes showed varied results on the competitive distance of HSR due to its relationship with the travel time.…”
Section: Introductionmentioning
confidence: 99%
“…However, in terms of transport structure, there are complementarities between the two. A large number of scholars started to study the air-rail intermodal component of the integrated transportation system [3,4]. Thus, it is important to study passenger travel choice behavior in terms of measuring the market advantages of different transportation modes and the rationality of resource allocation.…”
Section: Introductionmentioning
confidence: 99%